2019
DOI: 10.3390/rs11040465
|View full text |Cite|
|
Sign up to set email alerts
|

Detection and Validation of Tropical Peatland Flaming and Smouldering Using Landsat-8 SWIR and TIRS Bands

Abstract: A Tropical Peatland Combustion Algorithm (ToPeCAl) was first established from Landsat-8 images acquired in 2015, which were used to detect peatland combustion in flaming and smouldering stages. Detection of smouldering combustion from space remains a challenge due to its low temperature and generally small spatial extent. The ToPeCAl consists of the Shortwave Infrared Combustion Index based on reflectance (SICIρ), and Top of Atmosphere (TOA) reflectance in Shortwave Infrared band-7 (SWIR-2), TOA brightness tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…An important approach to study smouldering in field studies of peatlands is using infrared cameras due to larger scale of the spatial domain. Remote sensing of smouldering wildfires has attracted research interest to develop monitoring system using satellite data [21] or use of drones equipped with IR cameras. Compared to thermocouple measurements, infrared cameras offer the advantage of better spatial resolution and allow for a large burning area to be calculated.…”
Section: Introductionmentioning
confidence: 99%
“…An important approach to study smouldering in field studies of peatlands is using infrared cameras due to larger scale of the spatial domain. Remote sensing of smouldering wildfires has attracted research interest to develop monitoring system using satellite data [21] or use of drones equipped with IR cameras. Compared to thermocouple measurements, infrared cameras offer the advantage of better spatial resolution and allow for a large burning area to be calculated.…”
Section: Introductionmentioning
confidence: 99%
“…While relatively high intensity fires can be accurately detected via these datasets, cooler or smouldering fires, especially those commonly occur on degraded peatland may be more difficult to detect . A recent study has shown that VIIRS fire product has the accuracy of detecting the actual smouldering on peatland of 71% (Sofan et al 2019), suggesting that about a third of the actual smouldering events were potentially overlooked. MODIS fire product likely has lower detection accuracy than VIIRS data for smouldering fires due to the lower spatial resolution.…”
Section: Fire Occurrence Across Climate Land Types and Village Livelihoodsmentioning
confidence: 99%
“…Landsat-8 OLI & TIRS SWIR, TIR 16 30 Peatland fire detection at nighttime & daytime [26,27] BIRD HSRS MWIR, TIR 2-3 370 Peatland fire detection at daytime [28] TET-1 TET-1 MWIR 2-5 160 Peatland fire detection at daytime [29] Suomi NPP VIIRS SWIR 0.5 750…”
Section: Main Objective Referencementioning
confidence: 99%
“…However, because fire products are not available for Sentinel-2, there exists an opportunity for the development of a detection algorithm for this sensor. A fire detection algorithm, particularly for peatland fires in tropical environments, e.g., Indonesia, called Tropical Peatland Combustion Algorithm (ToPeCAl), has been established using aerosol, shortwave infrared (SWIR) and longwave thermal infrared (TIR) spectra and applied to Landsat-8 OLI/TIRS daytime [27].…”
Section: Main Objective Referencementioning
confidence: 99%